IMPROVEMENT OF THE NUTRITIONAL VALUE OF CORN FLOUR THROUGH FERMENTATION TECHNOLOGY USING MA-11 AND EM-4 - Anjani, Nova; Sukaryani, Sri (Universitas Veteran Bangun Nusantara, 2025)
This researchto determine the effect of corn tumpi fermentation with the addition of bioactivators MA-11 and EM-4 as well as urea and molasses on the content of BK, PK, and SK. The study was conducted at the Laboratory of the Faculty of Agriculture, Veteran Bangun Nusantara University for one month using a completely randomized design (CRD) with 3 treatments and 8 replications. The treatments were P0: 250 grams of corn tumpi + 2 grams of urea + 5 cc of molasses; P1: 250 grams of corn tumpi + 2% MA-11 + 2 grams of urea + 5 cc of molasses; P2: 250 grams of corn tumpi + 2% EM4 + 2 grams of urea + 5 cc of molasses. The results showed that the addition of MA-11 and EM-4 significantly increased the content of BK and PK, and also decreased the content of SK compared to the P0 / control treatment (P <0.01). Treatment P1 gave results that were not significantly different from treatment P2. The dry matter (DM) content in treatment P0 was 87.97%, P1: 88.65% and P2: 88.45%. Treatment P0 produced a crude protein (CP) content of 9.79%, P1: 11.37% and P2: 10.45%. The lowest crude fiber (CF) content was achieved by treatment P1 (3.70%) followed by treatment P2 (4.33%) and P0 (6.38%). The conclusion that can be drawn is that corn tumpi fermentation using MA-11 and EM4 with the addition of urea and molasses has a very significant effect on increasing CF content and decreasing CF content, but treatments P1 and P2 provide the same DM content. Bioactivator MA-11 provides a more effective effect than EM4 in increasing CF content and decreasing CF content.